In vivo evaluation of the reliability and validity of three digital occlusion analysis methods - Wang, Qing; Zhao, Zhe; Zhou, Ming; Zheng, Xiuli; An, Na; Niu, Lina; Tay, Franklin R.; Ma, Chufan; Wang, Fu (Journal of dentistry, 2022)
The reliability and validity of three digital occlusion analysis methods was evaluated in vivo. The three method evalueated were:scanning of articulating paper marks (SA), dental prescale occlusal analysis system (DP) and a virtual occlusion constructed method (VO). A conventional silicone transmission method (ST) was used as the standard for comparison. Each of the 20 enroled human subjects was tested with the four methods. Retest of each method was performed at 2-week intervals. Occlusal contact area (OCA) and occlusal contact numbers (OCN) were calculated for analyses. For reliability evaluation, intraclass correlation coefficients (ICC) of the OCA and OCN values obtained from each method were compared. For validity evaluation, Pearson correlations coefficients, paired t-tests, regression analysis and Bland-Altman analysis were examined. The ICC values of OCA and OCN were in the order: ST>SA>DP>VO. The highest OCA and OCN values were found ST while the lowest values were obtained from DP. Paired t-test identified a significant difference when OCA values obtained from the three digital methods were compared with ST, and between the OCN values of DP and ST. Pearson correlation showed high coefficients between ST and three digital methods (0.583–0.885 for OCA; 0.779–0.836 for OCN). A significant linear correlation was found between the results from ST and those from SA or VO. Bland-Altman analysis showed good agreement between OCN values of SA and ST, and between those of VO and ST. The three digital occlusal analysis methods showed good reliability and validity for in vivo clinical application. The three digital occlusion analysis systems examined demonstrate good potential in in vivo quantitative analysis, with good reliability and validity. The use of these analytical methods should facilitate digital workflow in clinical practice.